Pharmacokinetics, pharmacodynamics, and safety of izuforant, an H4R inhibitor, in healthy subjects: A phase I single and multiple ascending dose study - Byung Hak Jin; Taegon Hong; Byung Won Yoo; Choon Ok Kim; Dasohm Kim; Youn Nam Kim; Min Soo Park (Clinical and Translational Science)
Abstract Izuforant is a selective, and potent histamine H4 receptor (H4R) antagonist developed to treat atopic dermatitis (AD). There is an unmet medical need for therapeutic agents to control inflammation and pruritus. Izuforant is a strong candidate for this task based on the findings of non‐clinical studies showing that inhibition of the histamine‐mediated signaling pathway via H4R by izuforant results in decreased pruritus and inflammation. This study aimed to evaluate the clinical pharmacokinetic (PK) and pharmacodynamic (PD) profiles of izuforant. Dose‐block‐randomized, double‐blind, placebo‐controlled, single‐ and multiple ascending dose studies were conducted in 64 healthy volunteers. For the single ascending dose (SAD) study, 10–600 mg izuforant was administered to the designated groups. For the multiple ascending dose (MAD) study, 100–400 mg izuforant was administered to three groups. The clinical pharmacokinetic (PK) profile of izuforant was evaluated using plasma and urine concentrations. Blood sampling for the PD assay, which measured imetit‐induced eosinophil shape changes (ESC), was also conducted. A one‐compartment PK model described the distribution and elimination profiles of izuforant. An imetit‐induced ESC inhibition test was established and validated for PD evaluation as a measure of the H4R antagonistic effect. ESC inhibition was observed even at doses as low as 10 mg; however, this inhibition became stronger and lasted longer as the dose increased. All izuforant doses were well tolerated, and no discontinuations due to adverse events (AE) or deaths were reported.